Analisis Perbandingan Metode Penilaian Persediaan FIFO dan Rata-Rata terhadap Laba Perusahaan CV. Mitra Jaya Depok - Imas Tita Rosita; Rahmat Mulyana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2019)
This type of research used in this study is quantitative research, with data used are primary data sourced from the company itself and analyzed or calculated by the author. The statistics used are normality test, correlation test and T test (Paired Simple T Test) using SPSS version 23.Based on the results of the author's calculation and statistical analysis, it is known that the average valuation method is better used by the company compared to the FIFO method in terms of maximizing the profits obtained. The average method results in lower cost of goods sold compared to the FIFO method. For the FIFO method, the mean of profit is 453.909.147,7500, while for the average method, the mean of profit is 454.004.808,4650. Because the average value of the profits obtained in the FIFO method 453.909.147,7500 < the average method 454.004.808,4650 means that there is a descriptive difference on the average of the profits generated.